AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA BAGI PEMBANGUNAN - Enos Paselle; . Annivelorita; Sulis Setyawati; Teguh Riyanto; Ahmad Benni (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
This study describes the accountability of Village Fund Allocation (ADD) management from the village fund planning dimension and the village fund allocation dimensions. The research method used is a qualitative method with a descriptive approach. The results of the study indicate that the dimensions of village fund planning are carried out through village meetings and the dimensions of village fund allocation consider aspects of transparency and relevance of community needs.Keywords: accountability, village fund allocation